Clinical presentation and predictors of hospital mortality of diphtheria in Nigeria, July 2023 to April 2024: a single-center study - Abdurrazzaq Alege; Olayinka Rasheed Ibrahim; Rasheedat Mobolaji Ibraheem; Olajide Aladesua; Abubakar Sani Lugga; Yunusa Yusuf Yahaya; Abdallah Sanda; Bello Muhammed Suleiman (BMC Infectious Diseases)
Abstract Background Despite recurrent outbreaks of diphtheria in Nigeria, there is a lack of in-depth analysis of hospitalization outcomes. Herein, we describe the sociodemographic, clinical, and laboratory features associated with hospitalization outcomes (defined as death or discharge) during the recent diphtheria outbreak in Nigeria. Methods This prospective observational study included 246 confirmed diphtheria cases managed in a dedicated isolation ward of a health facility in northwestern Nigeria from July 1, 2023, to April 30, 2024. We analyzed clinical and laboratory features, immunization status, and socio-demographics in relation to hospitalization deaths using SPSS version 29. Results The median age (interquartile range) was 7.00 (4–10) years and 49.6% (122) were aged 5–10 years. Common clinical features were fever (95.9%), sore throat (91.9%), painful swallowing (90.7%), pseudomembrane (93.1%), and cervical-submandibular lymphadenopathy (91.5%). Most children were unvaccinated (158; 64.2%), 199 (80.9%) received diphtheria antitoxin, and both were related to outcomes. Mortality rate was 23.5% (58/246). After adjusting for confounders, predictors of hospitalization deaths were neck swelling with an adjusted odds ratio (AOR) of 9.80 (95% CI 1.68–56.47), abnormal respiratory findings (AOR, 149.99 [95% CI, 15.60–1442.02] ), hypoxemia (AOR, 37.79 [95% CI, 4.26–331.96] ), and elevated serum creatinine above 1.5 mg/dL (AOR 107.78, 95% CI, 7.94–1462.38). Conclusions Diphtheria is a significant burden in Nigeria, particularly among children. Neck swelling, hypoxemia, abnormal respiratory findings, and impaired renal function were predictive of hospitalization death. Although antitoxin and vaccination were related to outcomes, they did not predict hospitalization death.